Large‐Amplitude Thermal Vibration‐Coupled Valence Tautomeric Transition Observed in a Conductive One‐Dimensional Rhodium–Dioxolene Complex - Mitsumi, Minoru; Komatsu, Yuuki; Hashimoto, Masahiro; Toriumi, Koshiro; Kitagawa, Yasutaka; Miyazaki, Yuji; Akutsu, Hiroki; Akashi, Haruo (Chemistry : a European journal, 2021)
The exploration of dynamic molecular crystals is a fascinating theme for materials scientists owing to their fundamental science and potential application to molecular devices. Herein, a one‐dimensional (1D) rhodium‐dioxolene complex is reported that exhibits drastic changes in properties with the phase transition. X‐ray photoelectron spectroscopy (XPS) revealed that the room‐temperature (RT) phase is in a mixed‐valence state, and therefore, the drastic changes originate from the mixed‐valence state appearing in the RT phase. Another notable feature is that the mean square displacements of the rhodium atoms along the 1D chain dramatically increased in the RT phase, indicating a large‐amplitude vibration of the Rh−Rh bonds. From these results, a possible mechanism for the appearance of the mixed‐valence state in the RT phase was proposed based on the thermal electron transfer from the 1D d‐band to the semiquinonato π* orbital coupled with the large‐amplitude vibration of the Rh−Rh bonds. Vibronic interaction has the potential to create new fields on dynamic electronic states arising from the mixing of different electronic states by nuclear displacements. A one‐dimensional rhodium‐dioxolene complex undergoes drastic changes in properties with the phase transition, which are ascribable to the appearance of the mixed‐valence state due to the metal–ligand electron transfer coupled with a large‐amplitude vibration of Rh−Rh bonds.